With or without you: Effects of the concurrent range expansion of an herbivore and its natural enemy on native species interactions. (1st September 2017) - Carrasco, David; Desurmont, Gaylord A.; Laplanche, Diane; Proffit, Magali; Gols, Rieta; Becher, Paul G.; Larsson, Mattias C.; Turlings, Ted C. J.; Anderson, Peter
Abstract: Global climatic changes may lead to the arrival of multiple range‐expanding species from different trophic levels into new habitats, either simultaneously or in quick succession, potentially causing the introduction of manifold novel interactions into native food webs. Unraveling the complex biotic interactions between native and range‐expanding species is critical to understand the impact of climate change on community ecology, but experimental evidence is lacking. In a series of laboratory experiments that simulated direct and indirect species interactions, we investigated the effects of the concurrent arrival of a range‐expanding insect herbivore in Europe, Spodoptera littoralis, and its associated parasitoid Microplitis rufiventris, on the native herbivore Mamestra brassicae, and its associated parasitoid Microplitis mediator, when co‐occurring on a native plant, Brassica rapa . Overall, direct interactions between the herbivores were beneficial for the exotic herbivore (higher pupal weight than the native herbivore), and negative for the native herbivore (higher mortality than the exotic herbivore). At the third trophic level, both parasitoids were unable to parasitize the herbivore they did not coexist with, but the presence of the exotic parasitoid still negatively affected the native herbivore (increased mortality) and the native parasitoid (decreased parasitism rate), through failed parasitism attempts and interference effects. Our results suggest different interaction scenarios depending on whether S. littoralis and its parasitoid arrive to the native tritrophic system separately or concurrently, as the negative effects associated with the presence of the parasitoid were dependent on the presence of the exotic herbivore. These findings illustrate the complexity and interconnectedness of multitrophic changes resulting from concurrent species arrival to new environments, and the need for integrating the ecological effects of such arrivals into the general theoretical framework of global invasion patterns driven by climatic change. Abstract : Global warming may lead to the range expansion of multiple new species and to their integration in native interaction networks. Laboratory experiments with two associated exotic species showed that their effects on native species interactions depend on whether the new species arrive separately or concurrently: a concurrent arrival led to the formation of more interactions detrimental to native species.